The Effect of Bacteria Colony Pseudomonas fluorescens (UB_Pf1) and Bacillus subtilis (UB_Bs1) on the Mortality of Pratylenchus coffeae (Tylenchida: Pratylenchidae) - Presti Mardiyani Purwaningtyas; Bambang Tri Rahardjo; Hagus Tarno (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Parasitic Root-Lession nematode of Pratylenchus coffeae can reduce the Indonesian coffee plants productivity. Several studies reported that Pseudomonas fluorescens and Bacillus subtilis endophytic bacteria were antagonistic bacteria to nematode. The objective of this research was to reveal the effectiveness of bacterial colonies density of P. fluorescens (UB_Pf1), B.subtilis (UB BS1), and a combination of both bacteria on nematode mortality using median lethal concentration (LC50) and median lethal time 50 (LT50). The densities of bacteria used in this study were 107, 109, 1011 and 1013 cfu/ml. 35 testing nematodes were used and the mortality was counted at 6, 12, 24, 36, and 48 hours after treatments. The results showed that LC50 values of P. fluorescens was (UB_Pf1) was 4,3x108 cfu/ml, LC50 B. subtilis (UB_Bs1) was 1,9x109cfu/ ml, and LC50 combination of both bacteria was, 8x107 cfu/ml. It implies that the application of the combination of both bacteria are more pathogenic than single bacterial treatment. The results also showed that the highest LT50 value was 13.21 hours combination of bacterial colonies with a density of 1013 cfu/ml and the lowest LT50 value was 52.00 hours on P. fluorescens (UB_Pf1) treatment with colonies density of 107 cfu/ml.How to CitePurwaningtyas, P. M., Rahardjo, B. T., Tarno, H. (2016). The Effect of Bacteria Colony Pseudomonas fluorescens (UB_Pf1) and Bacillus subtilis (UB_Bs1) on the Mortality of Pratylenchus coffeae (Tylenchida: Pratylenchidae). Biosaintifika: Journal of Biology Biology Education, 8(3), 286-293.